Calcium carbide in anticipation and standardization of ripening in Cajá-manga fruits - Gomes, Francielly Rodrigues [UNESP]; da Silva, Danielle Fabíola Pereira; Costa, Gabriel Silva; de Souza, Pedro Henrique Magalhães; da Silveira-Neto, Américo Nunes; Cruz, Simério Carlos Silva (FapUNIFESP (SciELO), 2023)
Fruit ripening promoted by the exogenous application of ethylene an-alogs, such as calcium carbide, has commercial advantages. Thus, the knowledge of the responses of fruits treated with ethylene-inducing agents is essential to op-timize the use of these substances. This work aimed to evaluate the influence of exposure to calcium carbide on the anticipation and standardization of postharvest ripening of cajá-manga fruits. Physiologically mature fruits were exposed to calcium carbide for 24 hours at concentrations 0, 20, 40, 80, and 110 g m-3. The fruits were stored at a temperature of 28±2 °C and evaluated at 0, 2, 4, and 6 days for the loss of fresh mass, color of the epidermis and pulp given by the CIELAB color space, ti-tratable acidity, soluble solids content, the ratio between soluble solids content and titratable acidity, and vitamin C content. Cajá-manga fruits treated with different concentrations of calcium carbide had their ripening anticipated without compro-mising their characteristics. The concentrations of 20, 40, and 80 g m-3 of calcium carbide allowed the anticipation and standardization of fruit ripening within four days during storage, while for the highest concentration (110 g m-3), complete maturation was accelerated, occurring between two and four days of storage.
Carbureto de cálcio na antecipação e na uniformização do amadurecimento de frutos de Cajá-manga
Keywords: acetylene; fruit climatization; Spondias dulcis P